Eficacia del sistema dispatch en reducción de demoras e influencia en la productividad (acarreo) en inicios de turno - UM Pucamarca 2021 - Arias Jara, Erick Aramis (2023)
The following work presents the study carried out at the UM Pucamarca of the company MINSUR S.A on the issue of optimization of times and production at the beginning of each shift change. The mining sector is a very competitive environment, in which technologies are also developed and used to be effective and efficient in the production work carried out. These technologies allow delays in terms of productivity and operational delays to be resolved satisfactorily. Due to the foregoing, in this research work an opportunity for improvement was sought, since there were delays in the operation of MU Pucamarca from long ago. To this end, the solution was presented to create a strategic area for immediate Changing of the Guard in which a Dispatch System is implemented and to better control shift starts and production in general. Said solution was devised by analyzing historical production data and operational delays at the start of shift changes, resulting in notable deficiencies. Once the causes that were negatively impacting the operation were defined, we proceeded to analyze the strategic place for the implementation of the immediate Changing of the Guard area with the Dispatch System. The results of that implementation were positive, since operational delays related to shift change were reduced and production increased at the start of operations, resulting in significant savings of 91.3% and a favorable work evolution with increased productivity 146% at the start of each shift change.